2014
DOI: 10.1186/1471-2393-14-322
|View full text |Cite
|
Sign up to set email alerts
|

Medication exposure during pregnancy: a pilot pharmacovigilance system using health and demographic surveillance platform

Abstract: BackgroundThere is limited safety information on most drugs used during pregnancy. This is especially true for medication against tropical diseases because pharmacovigilance systems are not much developed in these settings. The aim of the present study was to demonstrate feasibility of using Health and Demographic Surveillance System (HDSS) as a platform to monitor drug safety in pregnancy.MethodsPregnant women with gestational age below 20 weeks were recruited from Reproductive and Child Health (RCH) clinics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
11
2
1
Order By: Relevance
“…Based on the entire pregnancy, prevalencesof 42% and 34% have been reported in Nigeria [ 16 ] and Ethiopia [ 12 ] respectively. Two studies in Nigeria [ 17 ] and Tanzania [ 18 ] reported higher prevalences (76%, and 94% respectively) of folic acid intake. However, these results were based on exposures across the entire pregnancy and are likely to decrease when restricted to the first trimester as studies in Africa have always reported a far greater proportion (about 40% greater) of medication exposure in the second and third trimesters compared to the first trimester [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the entire pregnancy, prevalencesof 42% and 34% have been reported in Nigeria [ 16 ] and Ethiopia [ 12 ] respectively. Two studies in Nigeria [ 17 ] and Tanzania [ 18 ] reported higher prevalences (76%, and 94% respectively) of folic acid intake. However, these results were based on exposures across the entire pregnancy and are likely to decrease when restricted to the first trimester as studies in Africa have always reported a far greater proportion (about 40% greater) of medication exposure in the second and third trimesters compared to the first trimester [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent pharmacovigilance study conducted on 994 pregnant females using the platform of the Rufiji Health and Demographic Surveillance System in Tanzania, found that more than 98% of these females reported taking at least one medication during pregnancy. 7 Analgesics were among the most frequently reported medications (24%). Paracetamol (acetaminophen) is a widely used analgesic and antipyretic.…”
Section: Bdnfmentioning
confidence: 99%
“…Since developing countries are facing several difficulties in setting up functional PV systems, this platform provided the opportunity to easily monitor and assess public health issues such as PV while significantly reducing the costs of implementation. 29,30 The aim of this study was to monitor passively versus actively adverse events (AEs) among the population living in Nanoro HDSS of Burkina Faso, who attended public health facilities and received an ACT (ASAQ or AL), and to assess the factors associated with the time of reporting a suspected ADR occurrence. In addition, through HDSS, the study aimed to monitor AEs in pregnant women who were inadvertently exposed to ACTs in the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%